2008
DOI: 10.1097/mlg.0b013e3181613ad2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Thyroid Cancer in Residents Surrounding the Three Mile Island Nuclear Facility

Abstract: Thyroid cancer incidence has not increased in Dauphin County, the county in which TMI is located. York County demonstrated a trend toward increasing thyroid cancer incidence beginning in 1995, approximately 15 years after the TMI accident. Lancaster County showed a significant increase in thyroid cancer incidence beginning in 1990. These findings, however, do not provide a causal link to the TMI accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
(63 reference statements)
1
23
2
Order By: Relevance
“…The study described increasing incidences of thyroid cancer in Lancaster and York counties starting 10 and 15 years after the TMI incident, but not in Dauphin County, where TMI is located. This increased incidence, however, did not correlate with the level of estimated ionizing radiation exposure in these counties 7…”
Section: Introductionmentioning
confidence: 69%
“…The study described increasing incidences of thyroid cancer in Lancaster and York counties starting 10 and 15 years after the TMI incident, but not in Dauphin County, where TMI is located. This increased incidence, however, did not correlate with the level of estimated ionizing radiation exposure in these counties 7…”
Section: Introductionmentioning
confidence: 69%
“…31 Although the Three Mile Island nuclear accident in central Pennsylvania released significant amounts of radioactivity, several studies have shown that the Three Mile Island accident is not likely to be responsible for large increases in the incidence of thyroid cancer in Pennsylvania. 12,32,33 By contrast, obesity and dietary habits may independently contribute to the development of thyroid cancer. 31,3437 According to Centers for Disease Control and Prevention data from 2010, Pennsylvania is the state with the 13th highest prevalence of obesity, with 29.1% of the population having a body mass index of 30 or greater (calculated as weight in kilograms divided by height in meters squared).…”
Section: Discussionmentioning
confidence: 99%
“…A causal relationship could not be established. [60] Other studies have also not been able to show definitive relationships.…”
Section: General Management: Security and Mass Triagementioning
confidence: 97%